CO2 Hydrogenation to Light Olefins Over In2O3/SAPO-34 and Fe-Co/K-Al2O3 Composite Catalyst - Numpilai T.; Kahadit S.; Witoon T.; Ayodele B.V.; Cheng C.K.; Siri-Nguan N.; Sornchamni T.; Wattanakit C.; Chareonpanich M.; Limtrakul J. (Springer, 2023)
Aluminum compounds; Carbon dioxide; Catalysts; Iron compounds; Light olefins; CO2 hydrogenation; Composite catalysts; Effect of catalyst; Efficient catalysts; Hydrocarbon product; Light olefins yield; Physical mixtures; Theoretical values; Indium compounds